2D Numerical Analysis of Shallow Foundation Rested Near Slope under Inclined Loading. (2016) - Baazouzi, Messaoud; Benmeddour, Djamel; Mabrouki, Abdelhak; Mellas, Mekki
Abstract: The bearing capacity of vertically loaded strip footing near slope in plane strain conditions has always been one of the subjects of major interest in geotechnical engineering for researchers and practical engineers. In the literature few studies deal with inclined loaded strip footings adjacent to a cohesionless slope. This study focuses on the numerical analysis of the bearing capacity for a strip footing near a cohesionless slope, and subjected to a centered inclined load, using the finite difference code Fast Lagrangian Analysis of Continua (FLAC). In this study, several geometrical and mechanical parameters have been considered in order to evaluate the effect of the slope on the bearing capacity. The obtained results are presented in terms of normalised failure envelopes in two-dimensional loading plane (H/Vo, V/Vo). The results show the influence of the load inclination and the position of the footing with respect to the slope on the bearing capacity.